PERSEPSI MAHASISWA JURUSAN PERBANKAN SYARI'AH UIN SUMATERA UTARA TERHADAP LAYANAN APLIKASI MOBILE BANKING BSI - Kiki Andrea Putri Hasibuan; Silvia Anggrie Nst; Dini Lestari; Muhammad Ikhsan Harahap (EKSYA : Jurnal Ekonomi Syariah, 2023)
Customers who are increasingly using digital services are used to and prefer services that are faster, transparent, comprehensive, and can be tailored to user needs. Customer interest is one aspect that can encourage a bank to achieve its goals, so a system is needed that answers the desire to meet the needs of banking services effectively and efficiently. Through the BSI mobile banking application, banks can play a role in meeting customer expectations. Therefore the purpose of this study is to determine the perceptions of Islamic banking students at UIN SU regarding convenience, speed, security, and satisfaction in using the BSI Mobile application. This study uses qualitative methods with data collection techniques through questionnaires and literature studies. The informants in this study were Islamic banking students at UIN SU who used the BSI mobile banking application. The results of this study indicate that students experience ease, speed, security and convenience in using BSI mobile application services.